WRITTEN BY TENTH GRADE STUDENTS AT SMK PAB 5 KLAMBIR LIMA - Mutiara Nur Fajrin; Masitowarni Siregar (Universitas Negeri Medan, 2021)
This study analyzed the Theme-Rheme system and the exchange of Themeand Rheme which called as Thematic Progression in studets’ writing. The mainpurpose of this study was to find out the Theme types and Thematic Progressionpatterns applied in students’ writing. The research design in this study wasqualitative. This study described how students develop recount text about theirpersonal experience. The researcher devided the subjects of this study into maleand female group which taken from students of SMK PAB 5 Klambir Lima. Thedata was collected through assigning the students to write a recount text genre.The results showed that the most applied Theme were Topical themes which actas participant or actor of the clause. The second Theme were Textual themeswhich act as conjunction in the clause. The last which also the least Theme wereInterpersonal Themes. The Interpersonal theme applied by students were theelements of comment adjunct and mood adjunct. Thematic Progression whichproposed by Eggins (1994) has three pattern; Contant Theme, Simple Linear, andMultipple Theme. The result in this study found there were only two patternsfound in students’ writing. The fisrt pattern was Constant Theme and the secodnpattern was Simple Linear.